Determination of the method of induction of mutations by gamma radiation in soybeans (Glycine max L. Merrill) for tolerance to carbonic rot produced by the fungus Macrophomina phaseolina (Tassi Goid.) - Antonio Samudio-Oggero; Héctor D. Nakayama N․; Gloría A. Resquín Romero; Wilson D. Romero Vergara; Oscar J. Vega Alvarenga; Juan V. Benítez Núñez; Benito Ortega Tórres; Pablo C. Caballero Romero; María C. Caridad González (MethodsX, 2025)
In recent years, there has been an increase in the appearance of charcoal root rot disease in soybeans crops (Glycine max L. Merril). Charcoal rot is caused by the soil-borne fungus Macrophomina phaseolina. This disease is typically exacerbated by water deficiency and high temperatures. To evaluate the soybean genotypes' response to this pathogen, novel genotypes developed through gamma irradiation of 150 Gy and 200 Gy were tested under, in field and greenhouse conditions. Additionally, total phenol content was analyzed as a potential indicator of plant tolerance. The results indicate that the incidence of disease in non-irradiated genotypes was 100 %, in genotypes irradiated with a dose of 150 Gy it was 87 %, and those irradiated with a dose of 200 Gy a 100 %. An increase in the level of total phenols was observed in the tolerant genotypes as well as some mutant genotypes with characteristics that show tolerance to the charcoal root rot disease. The results suggest that gamma radiation-induced mutation may be an effective method for breeding disease-resistant soybean varieties. • This variability method can be applied to any plant species. • This method can cause mutations in any part of the genome, this allows its application to be unlimited. • It is a method that can be used in a complementary way to other plant breeding methods.